Comparative study of gamma-irradiated PP and PE polyolefins part 2: Properties of PP/PE blends obtained by reactive processing with radicals obtained by high shear or gamma-irradiation. (15th January 2016) - Fel, Elie; Khrouz, Lhoussain; Massardier, Valérie; Cassagnau, Phlippe; Bonneviot, Laurent
Abstract: Compared with neat polypropylene (PP), the addition of low contents (typically <20wt %) of polyethylene (PE) can improve the impact strength of PP based blends. In order to improve tensile properties as well, reactive extrusion has been carried out with radicals obtained by high shear or γ-irradiation. The addition of a γ-irradiation step in the processing sequence, between extrusion and injection, can be considered as an efficient way for improving the properties of our PP/PE blends. The improvement of mechanical properties has been discussed in terms of creation of secondary interactions or covalent bonds at the interface of the γ-irradiated polymers, γ-PP and γ-PE. On one hand, the rheological measurements have highlighted an increase of the complex viscosity of the γ-irradiated blends at low frequencies. On the other hand, the EPR spectrum simulation shows that the radicals are not the same in the blend and in the genuine γ-PP and γ-PE. Besides, the increase of temperature in the sample affects the shape of the EPR spectra, revealing that some macroradicals react one to another, which creates new macroradical structures of rather alkoxyl type. Graphical abstract: Highlights: Addition of a γ-irradiation step in a PP/PE reactive blending. Radicals are not the same in our PP/PE blend and in the genuine γ-PP and γ-PE. Secondary interactions and covalent bonds at the interface of the γ-PP and γ-PE. Improvement of mechanical properties with γ-irradiation.